The University Students’ Perceptions on Instagram’s Translation Feature in Enhancing English Vocabulary Learning - Pratama, M. Hade; Dari, Tita Ratna Wulan (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study explored university students’ perceptions of Instagram’s translation feature in improving their English vocabulary learning. The research focused on two main questions: (1) how students view the usefulness of the feature, and (2) what difficulties they experience while using it. The purpose of this study was to investigate students’ opinions about the feature’s role in vocabulary learning and to identify the main challenges they encounter. A qualitative descriptive method was employed, involving 29 English Education students from Sriwijaya University selected through purposive sampling. The findings showed that students had varied perceptions toward Instagram’s translation feature. The highest average score appeared in the ease-of-use aspect (77.6%), suggesting that students found the feature simple and convenient to operate. In contrast, their perceptions of usefulness (52.6%) and contribution to vocabulary development (51.1%) were mostly neutral. This indicates that, although the feature helps students quickly grasp word meanings, they remain uncertain about its role in improving long-term vocabulary mastery. Several obstacles were also reported, including inaccurate or incomplete translations, technical issues, and untranslatable short captions. These results imply that while the translation feature is practical and supports incidental learning, it should not be viewed as a primary tool for learning English vocabulary. In conclusion, Instagram’s translation feature works most effectively as a supplementary aid when used alongside dictionaries, teacher support, and self-directed learning practices.